Clinical significance of SNP (rs2596542) in histocompatibility complex class I-related gene A promoter region among hepatitis C virus related hepatocellular carcinoma cases - Amal A. Mohamed; Ola M. Elsaid; Eman A. Amer; Heba H. Elosaily; Mohamed I. Sleem; Shawkat S. Gerges; Mohamed A. Saleh; Amal El Shimy; Yasmine S. El Abd (Journal of Advanced Research, 2017)
The major histocompatibility complex class I-related gene A (MICA) is an antigen induced by stress and performs an integral role in immune responses as an anti-infectious and antitumor agent. This work was designed to investigate whether (SNP) rs2596542C/T in MICA promoter region is predictive of liver cirrhosis (LC) and hepatocellular carcinoma (HCC) or not. Forty-seven healthy controls and 94 HCV-infected patients, subdivided into 47 LC and 47 HCC subjects were enrolled in this study. SNP association was studied using real time PCR and soluble serum MICA concentration was measured using ELISA. Results showed that heterozygous genotype rs2596542CT was significantly (P = 0.022) distributed between HCC and LC related CHC patients. The sMICA was significantly higher (P = 0.0001) among HCC and LC. No significant association (P = 0.56) between rs2596542CT genotypes and sMICA levels was observed. Studying SNP rs2596542C/T association with HCC and LC susceptibility revealed that statistical significant differences (P = 0.013, P = 0.027) were only observed between SNP rs2596542C/T and each of HCC and LC, respectively, versus healthy controls, indicating that the rs2596542C/T genetic variation is not a significant contributor to HCC development in LC patients. Moreover, the T allele was considered a risk factor for HCC and LC vulnerability in HCV patients (OR = 1.93 and 2.1, respectively), while the C allele contributes to decreasing HCC risk. Therefore, SNP (rs2596542C/T) in MICA promoter region and sMICA levels might be potential useful markers in the assessment of liver disease progression to LC and HCC.